Gender of supervisors. Does it matter? - Ropero-García, Miguel Ángel (My University, 2014)
This study analysed the effect on the wage gap of women´s access to supervisory jobs within each establishment in the Spanish labour market. Previous empirical studies have found that the promotion of women has a positive effect on the wage difference between genders. However, these studies did not take into account the endogeneity problem associated with job choice. We proposed a specific econometric specification to control for this problem under certain assumptions. Using matched employer-employee data from a sample of 213,709 workers, we found that an increase in the proportion of women among supervisors within each establishment significantly widens the wage difference between genders, but increases the presence of women in supervisory positions. This study shows that the impact of an increase in women´s power within establishments may well be more limited than other empirical studies suggest.
Keywords: Mujeres - Trabajo; Ejecutivas; Endogeneity problem; Probit; Supervisory jobs; Switching model